2017
DOI: 10.1088/1748-0221/12/11/c11010
|View full text |Cite
|
Sign up to set email alerts
|

Design advances of the Core Plasma Thomson Scattering diagnostic for ITER

Abstract: The Core Plasma Thomson Scattering (CPTS) diagnostic on ITER performs measurements of the electron temperature and density profiles which are critical to the understanding of the ITER plasma. The diagnostic must satisfy the ITER project requirements, which translate to requirements on performance as well as reliability, safety and engineering. The implications are particularly challenging for beam dump lifetime, the need for continuous active alignment of the diagnostic during operation, allowable neutron flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The use of such a short laser pulse has an impact also on other aspects of the system. First it will restrict the choice of the APDs to those with a sufficiently fast response time [12]. In addition it may help to mitigate the measurement noise due to the laser stray light.…”
Section: The Dtt Divertor Thomson Scattering Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of such a short laser pulse has an impact also on other aspects of the system. First it will restrict the choice of the APDs to those with a sufficiently fast response time [12]. In addition it may help to mitigate the measurement noise due to the laser stray light.…”
Section: The Dtt Divertor Thomson Scattering Systemmentioning
confidence: 99%
“…A second TS system is under study for DTT whose main purpose is to measure the T e and n e profiles in the central region of the plasma and, as in many other fusion experiments, provide also the information necessary to resolve the edge pedestal. For this system we have again followed a conventional approach, as for the divertor TS system, and have chosen to use the equatorial diagnostic port both for the input laser and for the collection optics, in a set-up similar to that foreseen for the ITER core TS system [12]. This set-up provides good accessibility to the edge region, where the highest resolution is required and the plasma conditions make the measurement more critical.…”
Section: The Dtt Core Thomson Scattering Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…We now calculate the expected performance of this hybrid TS set-up. We assume for the polychromator a set of spectral channels corresponding to the first six channels of the 8-channel set described in [14]. With this arrangement the low wavelength cut-off is at λ C = 587 nm and it has been shown that in these conditions the accuracy of the TS measurements obtained by the usual spectral analysis is somewhat limited at high T e .…”
Section: Expected Performancesmentioning
confidence: 99%
“…The 1319 nm lasers play a crucial role in laser medicine, optical communication, laser display, plasma research, nonlinear frequency and sodium atomic fluorescence detection at 80-110 km [1][2][3][4][5][6][7] . The 1319 nm laser is mainly generated by the transition between the R2 stark sublevel of the upper level 4 F3/2 and the X1 stark sublevel of the 4 I13/2 level (R 2 →X 1 ) of the Nd: YAG crystal, and the effective stimulated emission cross-section of the 1319 nm laser is about 0.95×10 -19 cm 2 [8] , which is one third of the 1064 nm laser transition.…”
Section: Introductionmentioning
confidence: 99%